Performance evaluation of quality improvement team in an anesthesiology department - Wang, Fu-Lan; Lee, Li-Chuan; Lee, Sheu-Hua; Wu, Shang-Liang; Wong, Chih-Shung (Acta anaesthesiologica Sinica, 2003)
In health care community, quality improvement pathway has always been treated as critical index to control cost, improve efficiency and promote service quality, particularly in the last decade. From theoretical standpoint, clinical practice as well as research data, quality improvement team has been demonstrated to play an important role in the adaptation to the changing health environment and enhancement of the competition through the improvement process. The purpose of this study was to explore members' job satisfaction, morale, organizational commitment and inventory management through quality improvement team intervention in a department of anesthesiology. This study was of a quasi-experimental and longitudinal design. The subjects involved 45 nurse anesthetists (the experiment group, intervention of quality improvement team) and 50 operation room nurses (control group) in a general hospital. The quality improvement team had been initiated and implemented pursuant to the quality improvement process for 8 months. GEEs (Generalized Estimating Equations) model was used to examine the differences in job satisfaction, morale, organizational commitment, and the inventory management was also examined between two groups. After control of all variables, except education background, such as age, marital status, education, position and nursing experience, a natural growth effect was observed on quality improvement team. The results revealed that the experimental group showed significant positive effects on both job satisfaction and organizational commitment after the intervention. The morale scale did not differ significantly between two groups. In the inventory management, the experimental group successfully decreased the monthly consumable materials stock with a descending rate of 24.8%, while in the control group, the inventory was increased 16.9% in the basal stock instead. As other previous reports did, the present study also demonstrated that intervention of the quality improvement team improves the nurse anesthetists' job satisfaction, such as promotion of autonomy, organizational policy and positive member interaction. Moreover, it improves work efficiency, service quality as well as control of the stock inventory.